2020
DOI: 10.1038/s41398-020-0807-9
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated reward activations associated with cannabis use in anxious/depressed individuals

Abstract: Individuals with mood/anxiety disorders may use cannabis for "self-medication," i.e., to induce positive mood or attenuate aversive mood states. However, little neurobiological evidence supports such use. The goal of this investigation was to test the hypothesis that cannabis use attenuates striatal response to reward in those with mood/ anxiety disorders. Reward-related processing was measured using a monetary incentive delay task under functional MRI. Individuals with any lifetime mood/anxiety disorder diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 46 publications
1
11
0
1
Order By: Relevance
“…In this work, we provide exemplar results 11 different pipelines (three pipelines on each of two fMRI tasks, four pipelines on resting-state fMRI, and one pipeline on resting EEG) to demonstrate the utility of our infrastructure. Additionally, ROI-level results from our standard pipelines have been used in studies of cannabis ( 29 ) and stimulant/opioid use ( 30 ), while voxelwise results have appeared in studies of neighborhood effects ( 31 ) and inflammation ( 32 ), and clinical data have been used to predict head motion during scanning ( 33 ). We have also used EEG derived features have to differentiate participants with mood and anxiety disorders from healthy controls ( 34 ) and to predict participant age ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we provide exemplar results 11 different pipelines (three pipelines on each of two fMRI tasks, four pipelines on resting-state fMRI, and one pipeline on resting EEG) to demonstrate the utility of our infrastructure. Additionally, ROI-level results from our standard pipelines have been used in studies of cannabis ( 29 ) and stimulant/opioid use ( 30 ), while voxelwise results have appeared in studies of neighborhood effects ( 31 ) and inflammation ( 32 ), and clinical data have been used to predict head motion during scanning ( 33 ). We have also used EEG derived features have to differentiate participants with mood and anxiety disorders from healthy controls ( 34 ) and to predict participant age ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we provide exemplar results 11 different pipelines (3 pipelines on each of 2 fMRI tasks, 4 pipelines on resting-state fMRI, and one pipeline on resting EEG) to demonstrate the utility of our infrastructure. Additionally, ROI-level results from our standard pipelines have been used in studies of cannabis (Spechler et al, 2020) and stimulant/opioid use (Stewart et al, 2020), while voxelwise results have appeared in studies of neighborhood effects (Feng et al, 2019) and inflammation (Burrows et al, 2021), and clinical data have been used to predict head motion during scanning (Ekhtiari et al, 2019). We have also used EEG derived features have to differentiate participants with mood and anxiety disorders from healthy controls (Al Zoubi et al, 2019) and to predict participant age (Al Zoubi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported apathy and anhedonia in cannabis users (81)(82)(83), while others failed to detect this phenomenon (84)(85)(86). Decreased cerebral activation in response to reward is reduced in cannabis users, and more so in those with recent heavy CU (87). Although CU may contribute to anhedonia, additional data indicate that anhedonia in adolescence may predispose to CU (88).…”
Section: Influence Of Cannabis On the Course And Clinical Presentation Of Depressionmentioning
confidence: 99%